Assessing China’s Legal Reforms - Liebman, Benjamin L. (Columbia Journal of Asian Law, 2009)
Over the past thirty years China has engaged in what is perhaps the most rapid development of any legal system in the history of the world. The Chinese legal system has been fundamentally transformed since 1978. At the beginning of the reform era there were few laws or trained personnel. Today, China has sophisticated legal institutions, thousands of laws and regulations, and the third largest number of lawyers in the world. Law has begun to regulate both state and individual behavior in ways that were inconceivable in 1978. Commitment to the rule of law has become an important part of state ideology and state legitimacy. Popular understanding of law has expanded dramatically and the legal system has become an important route for addressing grievances and resolving disputes.